anonymous
  • anonymous
For questions 10–11, find the solutions of the system. 10. y = x² + 3x – 4 y = 2x + 2 (a) (–3, 6) and (2, –4) (b) (–3, –4) and (2, 6) (c) (–3, –4) and (–2, –2) (d) no solution 11. y = x² – 2x – 2 y = 4x + 5 (a) (–1, 1) and (–7, –23) (b) (–1, 1) and (7, 33) (c) (–1, 33) and (7, 1) (d) no solution thankyou!!!
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Callisto
  • Callisto
For 10 y = x² + 3x – 4 -(1) y = 2x + 2 -(2) (1) - (2) 0 = x² + 3x – 4 -(2x+2) 0 = x² +x -6 Can you solve for x and y from here?
anonymous
  • anonymous
not really
Callisto
  • Callisto
Alright , do you understand so far?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
i think
Callisto
  • Callisto
then i'll continue.. 0 = x² +x -6 0 =(x+3)(x-2) x = -3 or x=2 Put x=-3 into y = 2x + 2 y = 2(-3) + 2 = -2 Put x=2 into y = 2x + 2 y = 2(2) + 2 =6 Can you choose the answer for 10 now?
Callisto
  • Callisto
Sorry.. for the middle part, it should be like this Put x=-3 into y = 2x + 2 y = 2(-3) + 2 = -4
Callisto
  • Callisto
For 11, it's similar to 10 y = x² – 2x – 2 -(1) y = 4x + 5 -(2) (1) -(2) 0 = x² – 2x – 2 -(4x + 5) 0 = x² - 6x -7 Can you do it from here then?
anonymous
  • anonymous
A plot is attached.
1 Attachment

Looking for something else?

Not the answer you are looking for? Search for more explanations.